2001
DOI: 10.4269/ajtmh.2001.64.303
|View full text |Cite
|
Sign up to set email alerts
|

Increased multiplicity of Plasmodium falciparum infections and skewed distribution of individual msp1 and msp2 alleles during pregnancy in Ndiop, a Senegalese village with seasonal, mesoendemic malaria.

Abstract: Abstract. Pregnancy is associated with a greater susceptibility to Plasmodium falciparum infections, which may result in serious complications affecting both the mother and the fetus. To compare allelic diversity and multiplicity of infection in the same women during and outside pregnancy, we conducted a retrospective analysis of the monthly fingerprick blood samples collected during a longitudinal survey conducted in Ndiop, a Senegalese village with mesoendemic malaria. Merozoite surface protein-1 (msp1) bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
2
22
1
1
Order By: Relevance
“…This finding is characteristic of areas with unstable malaria transmission and has also been reported among pregnant women in Senegal (Schleiermacher et al, 2001). …”
Section: Discussionsupporting
confidence: 78%
“…This finding is characteristic of areas with unstable malaria transmission and has also been reported among pregnant women in Senegal (Schleiermacher et al, 2001). …”
Section: Discussionsupporting
confidence: 78%
“…Some of these studies used gel based PCR-RFLP analysis methods, and reported MOIs ranging from 1.5 to 4 [27], [28]. Another study used a quantitative Gene scan method and found a MOI of 5.6, suggesting that more sensitive methods are likely to detect higher MOIs [29]. The studies conflicted on the relationship between gravidity and MOI, with one study finding a negative correlation [29], and another finding no association [27].…”
Section: Resultsmentioning
confidence: 99%
“…19,[22][23][24] The number of genotypes has been found to decrease with gravidity in some studies, 23,24 but not in others. 19,25 In Ngali II, women were bitten at least once every other day by an infected mosquito.…”
Section: Discussionmentioning
confidence: 96%
“…19,20 This assay is a standard approach for studying genetic diversity of P. falciparum , 18,20 including in pregnant women. 19,[21][22][23][24][25] The number of alleles at the two loci was determined and the locus with the largest number of bands was used to estimate the MoI. In addition, the C-terminus of MSP-1 was sequenced and the MSP1-19 type was determined based on amino acids at position 294, 341, 349, 350, 351, and 366 of the MSP-1 42 3D7 reference sequence.…”
Section: Study Population Between January 2001 and May 2005mentioning
confidence: 99%